Purified Escherichia coli recA protein catalyzes homologous pairing of superhelical DNA and single-stranded fragments. - Shibata, T (1979)
Purified Escherichia coli recA protein catalyzed ATP-dependent pairing of superhelical DNA and homologous single-stranded fragments. The product of the reaction: (i) was retained by nitrocellulose filters in 1.5 M NaCl/0.15 M Na citrate at pH 7, (ii) was dissociated at pH 12.3 but was not dissociated by heating at 55 degrees C for 4 min or by treatment with 0.2% sodium dodecyl sulfate and proteinase K, (iii) contained covalently closed circular double-stranded DNA (form I DNA), (iv) contained single-stranded fragments associated with replicative form (RF) DNA, and (v) contained a significant fraction of D-loops as judged by electron microscopy. Linear and nicked circular double-stranded DNA did not substitute well for superhelical DNA; intact circular single-stranded DNA did not substitute well for single-stranded fragments. Homologous combinations of single-stranded fragments and superhelical DNA from phages phiX174 and fd reacted, whereas heterologous combinations did not. The reaction required high concentrations of protein and MgCl2. The ATPase activity of purified recA protein was more than 98% dependent on the addition of single-stranded DNA. In 1 mM MgCl2, the ability of superhelical DNA to support the ATPase activity was two-thirds as good as that of single-stranded DNA.